A Novel Plaster Dressing: A Combination of Chicken Eggshell Hydrogel Plus Button-Fungus Extract Enhances Wound Healing in Diabetic Patients - Rafiqi, Akbar; Nabilatusyifa, Alivianisa; Putri, Oyi Candra Santoso; Hasanah, Ikromatul; Rahmah, Sabrina Firdayani; Andrianto, Dimas (Current Biochemistry, 2023)
Diabetic patients are susceptible to severe wound conditions due to high blood sugar levels and bacterial infections. This study aims to determine the formulation and effectiveness of the hydrogel plaster combination of laying hen eggshells with button mushrooms in curing diabetic wounds. The research methods consisted of making the hydrogel, coagulation test, and antibacterial tests. Hydrogels were made with 5%, 10%, and 20% eggshell concentrations. The coagulation activity test used rabbit blood, which was added with glucose. Antibacterial test was performed using Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli). This research shows that the coagulation activity of F2 and F3 formulations significantly differed from the control, with an average blood clotting time of 64.67 minutes and 63.00 minutes. The antibacterial test results produced a clear zone for S. aureus and E. coli with diameters of 10.27 mm and 9.18 mm for F2, 6.90 mm, and 11.66 mm for F3. This research concludes that hydrogel formulation 3, with 20% eggshell and 6.4% button mushroom, had the best blood clotting effect and antibacterial activity.